Nitric Oxide and Modulatory Effects of the Root extracts of Phlogacanthus tubiflorus against Oxidative Stress induced by Hydrogen Peroxide - Hussain, Anowar; Saikia, Viveeyan; Ramteke, Anand (Free Radicals and Antioxidants)
Introduction: Nitric oxide (NO) mediated signaling is known to influences tumor progression and has been implicated as a novel therapeutic target cancer therapy. Methods: In the present study, we have reported the modulatory effects of the root extracts of Phlogacanthus tubiflorus on NO levels in the lymphocytes cultured in vitro and exposed to oxidative stress induced by H2O2. Results: Increase in the levels of NO was observed in the lymphocyte treated with increasing concentration of H2O2 (0.1, 0.2, 0.5 and 1.0%), but the cell viability declined significantly. Treatment of Lymphocyte with root extract resulted in the decrease of NO level and increase in the Cell Viability. We also observed declined in NO levels and increase in cell viability in the lymphocyte pre-treated with the different concentrations of (50, 100, and 200 μg/ml) of root extracts and followed by the 1% H2O2 treatment. Conclusion: The present data suggests that NO and cell viability are inter related and extract used is rich in phytochemicals with modulatory effect on both NO and cell viability and hence, might find relevance in chemoprevention of oxidative stress related diseased conditions.
Keywords: Chemo-modulation; Nitric Oxide; Oxidative stress; Phlogacanthus tubiflorus